Developing employee capital : setting the stage for lifelong learning - Kalamas, David J. (HRD Press, 2004)
Make employees responsible for their own success. Ready to take the next step in employee development? This innovative book provides guidelines for helping managers create work environments where employees can develop themselves, without a great deal of direction. What's in it for you and your organization? Employees who are skilled at the process of self-development are independent learners and thinkers who are more knowledgeable about the organization, less likely to exit, better able to respond to changing market conditions, and more positive about their jobs. Bottom line: They are more.